2021
DOI: 10.1177/1356336x211002855
|View full text |Cite
|
Sign up to set email alerts
|

Students’ experiences and learning of social inclusion in team activities in physical education

Abstract: Physical education (PE) can be a context in which students are ‘educated through the physical’, which includes the possibility to learn social inclusion as an important life skill and contributor to the greater good of society. A key goal in the Norwegian educational system is that such positive life skills become internalised in students. The aims of this study were to understand students’ experiences of and behaviour towards social inclusion – such as passing the ball – in team activities and how the teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…During a seven-session pedagogical intervention based on a championship using the Marro (Prisoner's Bar) game, the characteristics of the Marro League obliged the participants to consider two aspects: (a) the objective of the game, scoring according to the outcome of the game; and (b) relationship with peers or opponents, a subjective score on the level of competence of the students aimed at educating aspects such as self-esteem, empathy, respect, effective communication, and others [48]. In another paper aiming to understand students' experiences and behaviour towards social inclusion-such as passing the ballin team activities and how the teacher facilitated the learning of social inclusion [49], researchers argued for a more integrative approach than the one they had observed. Indeed, learning to pass the ball through external control (i.e., teacher's instruction) is not the same as understanding why one should pass the ball.…”
Section: Discussionmentioning
confidence: 99%
“…During a seven-session pedagogical intervention based on a championship using the Marro (Prisoner's Bar) game, the characteristics of the Marro League obliged the participants to consider two aspects: (a) the objective of the game, scoring according to the outcome of the game; and (b) relationship with peers or opponents, a subjective score on the level of competence of the students aimed at educating aspects such as self-esteem, empathy, respect, effective communication, and others [48]. In another paper aiming to understand students' experiences and behaviour towards social inclusion-such as passing the ballin team activities and how the teacher facilitated the learning of social inclusion [49], researchers argued for a more integrative approach than the one they had observed. Indeed, learning to pass the ball through external control (i.e., teacher's instruction) is not the same as understanding why one should pass the ball.…”
Section: Discussionmentioning
confidence: 99%
“…Although direct instruction has commonly been branded ineffective, as it is assumed to reduce students to passive learners, this research has shown that, when combined with structured assignments and teacher guidance, direct instruction can facilitat e the achievement of learning goals. Second, three variables should be carefully considered when preparing learning activities (1) condition, (2) method, and (3) learning results [51][52][53]. The condition variable consists of the purpose and characteristics of the learning materials and the challenges and characteristics of the students; the method variable consists of the strategies used for organizing, implementing, and administering the learning processes; and the learning results consist of the effectiveness, efficiency, and appeal of the process.…”
Section: Success Preparing Items That Adhere To Grammatical Conventionsmentioning
confidence: 99%
“…Beberapa tema penelitian utama telah muncul dari studi dalam pendidikan jasmani inklusi, seperti pengalaman siswa dan pembelajaran inklusi sosial dalam pendidikan jasmani (Hovdal et al, 2021), mempromosikan penerimaan sosial dan inklusi dalam pendidikan jasmani (O'Neil & Olson, 2021), pendidikan inklusi dalam pendidikan jasmani dari sudut pandang penyandang disabilitas (Widyawan, 2020), dan pembuatan instrumen efikasi diri guru pendidikan jasmani menuju inklusi (M E Block et al, 2013). Namun, belum ditemukan pembahasan dalam perspektif sosial budaya di Indonesia.…”
Section: Pendahuluan Pendahuluanunclassified